2020
DOI: 10.1038/s41598-019-57176-2
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD93 in allergic asthma

Abstract: Jung-Won park 2,3 & Jae-Hyun Lee 2,3* CD93 has been shown critical roles in inflammatory and immune diseases. However, in allergic asthma, the potential roles of soluble CD93 (sCD93) have not been well studied. We conducted house dust mite (HDM) stimulation with Der p 1 in BEAS-2B and U937 cells, followed by treatment with dexamethasone or small interfering RNA against CD93. A HDM-induced murine allergic asthma model was also established. We estimated the power of sCD93 to predict allergic asthma in a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…CD93, also called complement component C1q receptor or C1QR is considered to be associated with various inflammatory diseases, including asthma. Studies have shown increased serum CD93 levels in patients with stable asthma [38], as well as increased serum CD93 levels during asthma exacerbations that decrease after treatment [39]. In agreement with these studies, we have also observed increased abundance of CD93 in the small airway lining fluid in patients with asthma, suggesting an increased leucocyte migration, complement activation, and clearance of apoptotic cells in the small airways of these subjects [39].…”
Section: Discussionsupporting
confidence: 90%
“…CD93, also called complement component C1q receptor or C1QR is considered to be associated with various inflammatory diseases, including asthma. Studies have shown increased serum CD93 levels in patients with stable asthma [38], as well as increased serum CD93 levels during asthma exacerbations that decrease after treatment [39]. In agreement with these studies, we have also observed increased abundance of CD93 in the small airway lining fluid in patients with asthma, suggesting an increased leucocyte migration, complement activation, and clearance of apoptotic cells in the small airways of these subjects [39].…”
Section: Discussionsupporting
confidence: 90%
“…Increased expression of membrane CD93 was observed on activated macrophages along with increased concentrations of sCD93 in plasma [ 5 ]. Consequently, increased circulating sCD93 was observed in acute and chronic inflammatory conditions in human, including myocardial infarction [ 12 ], autoimmune [ 13 , 14 , 15 , 16 ] and allergic diseases [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, these tests may not help to define the underlying airway inflammation. That's why recent asthma research is focusing on non-invasive and reliable cellular, soluble and genetic biomarkers 12 .…”
Section: Discussionmentioning
confidence: 99%